Impact of HEC-Based Teachers Training Programs on Job Performance of University Teachers (Journal of Asian Development Studies, 2013)
Educational institutions are responsible for producing market compatible labor force and well-educated members of the society. These institutions could find the target by employing qualified, experienced and dynamic teaching staff. To cater with recent educational challenges faculty refresher courses and on job trainings workshops are considered more productive. For the reason Higher Education Commission of Pakistan (HEC) has initiated Faculty Professional Development Program (FPDP) and Professional Competency Enhancement Program for Teachers (PCEPT) since 2004. This study is to investigate the impact of HEC based university teachers training programs on skills enhancement and professional development of teachers. The population of the survey study is the university teachers who get benefit from these HEC training programs. About 37 respondents are randomly selected for the data collection. The results of the study shows that irrespective to the gender overall respondents agree that these programs enhance their professional competence. Explicitly participants view topmost improvement in communication skills, while lowest impact on research skills due to these training programs. Moreover, the participants of FPDP claim higher learning outcomes comparing to PCEPT.